Oral Lesions in HIV-Positive Patients:A Retrospective Study from aHistopathology Service (Revista da Faculdade de Odontologia - UPF, 2025)
Aim: HIV-associated oral lesions may serve as predictive indicators of immunosuppression, assisting inboth the diagnosis and monitoring of disease progression in affected patients. Therefore, this study aimedto retrospectively analyse biopsied HIV-associated oral lesions diagnosed by a specialised histopathologyservice, with emphasis on patient and lesion characteristics. Materials and methods: A retrospectivecross-sectional study was conducted to analyse cases of HIV-associated oral lesions from the DCOD,covering records from January 1981 to December 2024. Results: Among the 26,947 reports analysed, 83were suggestive of HIV-associated lesions, of which 24 patients had confirmed infection. Kaposi sarcomaand non-Hodgkin lymphoma were the most frequent diagnoses. Most patients were male (75%), with amean age of 46 years (SD = 14.91). Conclusion: This retrospective study met its objectives bycharacterising the demographic profile of affected patients and describing the clinical features ofHIV-associated oral lesions diagnosed at a regional referral centre